Role of epithelial to mesenchymal transition associated genes in mammary gland regeneration and breast tumorigenesis. Issue 1 (December 2017) - Sikandar, Shaheen; Kuo, Angera; Kalisky, Tomer; Cai, Shang; Zabala, Maider; Hsieh, Robert; Lobo, Neethan; Scheeren, Ferenc; Sim, Sopheak; Qian, Dalong; Dirbas, Frederick M.; Somlo, George; et al.
Abstract Previous studies have proposed that epithelial to mesenchymal transition (EMT) in breast cancer cells regulates metastasis, stem cell properties and chemo-resistance; most studies were based on in vitro culture of cell lines and mouse transgenic cancer models. However, the identity and function of cells expressing EMT-associated genes in normal murine mammary gland homeostasis and human breast cancer still remains under debate. Using in vivo lineage tracing and triple negative breast cancer (TNBC) patient derived xenografts we demonstrate that the repopulating capacity in normal mammary epithelial cells and tumorigenic capacity in TNBC is independent of expression of EMT-associated genes. In breast cancer, while a subset of cells with epithelial and mesenchymal phenotypes have stem cell activity, in many cells that have lost epithelial characteristics with increased expression of mesenchymal genes, have decreased tumor-initiating capacity and plasticity. These findings have implications for the development of effective therapeutic agents targeting tumor-initiating cells. The contribution of EMT in mammary gland homeostasis and human breast cancer is still unclear. Here, using in vivo lineage tracing and breast cancer PDXs the authors demonstrate that the repopulating capacity in normal mammary epithelial cells and tumorigenic capacity in breast cancer is independent of expression of EMT-associated genes.